Analysis of project-based learning implementation on Indonesian language mastery of fifth-grade students - Anisa Anggi Febrianti; Lina Putriyanti; Sukamto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The present study analyzes the process and impact of implementing the PjBL model on fifth-grade elementary students’ mastery of Indonesian language materials. The study employed a qualitative approach, with data collected through observation, interviews, tests, and documentation. The tests were used to support qualitative findings rather than for quantitative analysis. The study focused on implementing the PjBL model and assessing its impact on students’ mastery of the learning materials. The findings reveal that implementing the PjBL model successfully created meaningful learning experiences. Pre-test results indicate differences in students’ initial achievement levels. After implementing the PjBL model, students’ learning outcomes improved, particularly among those who previously scored lower, while the highest scores remained relatively stable. These results indicate an overall improvement in students’ understanding of the material, as reflected in increased scores. Interview findings reveal that students were more actively engaged, more motivated, and found it easier to understand the material through direct participation in project-based activities. This study is expected to contribute to educational research by enhancing understanding of the implementation of the PjBL model in elementary schools and to serve as a reference for educators and future researchers.